Strengthening rectangular beams with NSM steel bars and externally bonded GFRP - Wuertz, Augustine F. (Kansas State University, 2013)
The technology of FRP strengthening has matured to a great extent. However, there is always room for performance improvements. In this study, external bonding of GFRP and near surface mounting (NSM) of regular steel bars is combined to improve the behavior, delay the failure, and enhance the economy of the strengthening. E-Glass FRP is selected due to its inexpensive cost and non-conductive properties to shield the NSM steel bars from corrosion. On the other hand, the use of NSM bars gives redundancy against vandalism and environmental deterioration of the GFRP. An experimental program is conducted in which four rectangular cross-section beams are designed, built, and tested in four-point bending. The first beam is tested as a control beam failing at about 12.24 kips. The second beam is strengthened using two #5 steel NSM bars and 1 layer of GFRP, both extending to the support. This beam failed at 31.6 kips. The third beam is strengthened with the same system used for the second beam. However, the NSM steel bars were cut short covering 26% of the shear-span only while the GFRP was extended to the support. This beam failed at 30.7 kips due to reaching the full flexural capacity of the section at the NSM bars cut off point and the shear stress concentration at the steel bar cut off point. The fourth beam was strengthened with same system as the third beam but then submerged in a highly concentrated saline solution for six months and then tested. This beam failed at a maximum applied load of 29.8 kips, which shows that the GFRP sheet provided good corrosion resistance from the saline solution.
Keywords: GFRP; NSM; Externally bonded; Strengthening; Concrete; Civil Engineering (0543)